2023
DOI: 10.1002/viw.20220065
|View full text |Cite
|
Sign up to set email alerts
|

CBT‐Cys click reaction for optical bioimaging in vivo

Abstract: Derived from the D‐luciferin regeneration pathway in firefly body, the click condensation reaction between 2‐cyanobenzothiazole (CBT) and D‐cysteine (Cys) (CBT‐Cys click reaction) possesses unique advantages, including superior biocompatibility, high second order reaction rate, and metal‐free mild conditions, emerging as a powerful bioorthogonal tool for a variety of chemical biological applications. Moreover, owing to its programmable controllability (e.g., pH, reduction, or enzyme), CBT‐Cys click reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…16 Recently, the stimuli-mediated approach on the basis of the rapid condensation reaction between 2-cyanobenzothiazole (CBT) and D-cysteine (Cys) has shown great promise for amplifying imaging signals. 17,18 Nevertheless, the CBT-Cys condensation reaction may be influenced due to a high concentration of endogenous free Cys. 19 To settle the issue, our group designed a new molecular scaffold SF, which can reduce the interference of free cysteine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Recently, the stimuli-mediated approach on the basis of the rapid condensation reaction between 2-cyanobenzothiazole (CBT) and D-cysteine (Cys) has shown great promise for amplifying imaging signals. 17,18 Nevertheless, the CBT-Cys condensation reaction may be influenced due to a high concentration of endogenous free Cys. 19 To settle the issue, our group designed a new molecular scaffold SF, which can reduce the interference of free cysteine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both of these two click reactions can be easily activated by relevant stimuli within the body (e.g., pH, reduction, or enzymes). Among these stimuli, enzymes as ubiquitous active substances in organisms and play pivotal roles in numerous physiological and pathological processes. , Extensive research has consistently demonstrated a direct correlation between aberrant enzyme expression and various diseases, thereby establishing that enzymes as widely acknowledged crucial biomarkers for multiple ailments may contribute to more precise molecular imaging . Harnessing the potential of enzymes facilitates the development of “smart” probes, which can offer enhanced imaging contrast compared with conventional probes and thereby realize more accurate disease diagnoses …”
Section: Introductionmentioning
confidence: 99%
“…As our group and other groups found, these CAs enabled enhanced T 1 -weighted MRI of pathological analytes at low magnetic fields (e.g., 0.5 T, 1.0 T) with superior selectivity, sensitivity, and tumor retention. In 2014, Ye et al proposed a Gd-based self-assembling probe for MRI imaging of apoptosis in vivo , in which the probe was able to form intramolecular cyclic structures through a reaction between 2-cyano-6-hydroxyquinoline (CHQ) and d -cysteine (CHQ-Cys). , In fact, CHQ-Cys is a modified version of the reaction between 2-cyanobenzothiazole (CBT) and d -cysteine (CBT-Cys). CBT-Cys is an original click reaction derived from the d -luciferin regeneration pathway in the firefly body and has been employed to fabricate versatile self-assembling probes for expanded bioapplications since 2010. In terms of biocompatibility, we believe that CBT-Cys has better potential over CHQ-Cys for in vivo applications, owing to its “firefly-derived” nature. This motivated us (and we were also inspired by the work of Ye et al) to design a “smart” Gd-based CBT-Cys probe to study apoptosis in vivo , which has not been reported.…”
mentioning
confidence: 99%